2014
DOI: 10.1136/annrheumdis-2014-eular.3811
|View full text |Cite
|
Sign up to set email alerts
|

SAT0052 Influence of Immunogenicity and Drug Levels on the Efficacy of Long-Term Treatment of Rheumatoid Arthritis with Adalimumab and Etanercept: A Uk-Based Prospective Study

Abstract: Background The introduction of tumour necrosis factor inhibitors represents a major advance in the treatment of rheumatoid arthritis (RA). Despite this, up to 40% of patients fail to respond- either due to primary inefficacy or loss of response. One explanation is immunogenicity leading to the development of anti-drug antibodies (ADAb) and low drug levels. Radioimmunoassay (RIA) is a sensitive method to detect ADAb and is less prone to drug interference vs. ELISA. The clinical utility of pharmacological monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In many of the included studies in which the type of immunoassay was identified and pharmacokinetic or clinical outcomes evaluated, the presence of ADA was associated with decreased efficacy [20 of 38 (53%) adalimumab studies and 26 of 62 (42%) infliximab studies; Tables and ]. In adalimumab studies conducted in patients with RA using several different assay formats, ADA‐positive patients had significantly less improvement in clinical symptoms with treatment , were significantly more likely to have poor response or treatment failure and were significantly less likely to achieve clinical remission or low disease activity compared with ADA‐negative patients. Similar results were observed in infliximab studies in RA regardless of immunoassay type .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many of the included studies in which the type of immunoassay was identified and pharmacokinetic or clinical outcomes evaluated, the presence of ADA was associated with decreased efficacy [20 of 38 (53%) adalimumab studies and 26 of 62 (42%) infliximab studies; Tables and ]. In adalimumab studies conducted in patients with RA using several different assay formats, ADA‐positive patients had significantly less improvement in clinical symptoms with treatment , were significantly more likely to have poor response or treatment failure and were significantly less likely to achieve clinical remission or low disease activity compared with ADA‐negative patients. Similar results were observed in infliximab studies in RA regardless of immunoassay type .…”
Section: Resultsmentioning
confidence: 99%
“…In many of the included studies in which the type of immunoassay was identified and pharmacokinetic or clinical outcomes evaluated, the presence of ADA was associated with decreased efficacy [20 of 38 (53%) adalimumab studies and 26 of 62 (42%) infliximab studies; Tables 2 and 3]. In adalimumab studies conducted in patients with RA using several different assay formats, ADA-positive patients had significantly less improvement in clinical symptoms with treatment [45,46], were significantly more likely to 100…”
Section: Impact Of Ada Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the complex formed by an anti-TNF drug and its specific antibody may affect its pharmacokinetics by increasing its clearance and lowering its serum level, thus having a potentially negative impact on clinical responses. A recently reported randomized controlled trial (RCT) and real-life data showed that anti-drug antibody-positive patients treated with ADA, IFX, CZP, or GLM had lower serum bD-MARD levels than those who are anti-drug antibody-negative [21,[30][31][32][33]. However, although one study found that serum IFX levels were low ( < 0.5 µg/mL) in one-quarter of RA patients, no more than 11% had detectable anti-IFX antibodies, suggesting that additional factors may be responsible for the reduced efficacy of IFX [34].…”
Section: Immunogenicity Of Anti-tnf Agents In Ramentioning
confidence: 99%
“…In a UK study of over 300 RA patients, body mass index (BMI) was the strongest predictor of low drug levels and subsequent poor response. 40 Overweight patients are recognized to be underdosed on subcutaneous anti-TNF drugs. 41 The sampling date within a 2-week drug injection interval to obtain a trough measurement in TDM could be important: is within 3 days of drug administration acceptable, or could this be extended to up to 1 week?…”
Section: Challenges For Tdm In Rheumatologymentioning
confidence: 99%